Adolescents and spiritualism: is this a good way to cope with fear? A qualitative approach - Mathijsen, François P. (Mental health, religion & culture, 2012)
Two qualitative studies complement existing literature on coping and paranormal belief, by analysing the link between paranormal experiences of spiritualism and coping. Thirty-six semi-directive interviews of young people aged between 12 and 18 (M = 15, SD = 1.3) and 13 non-directive "life story" interviews with young people aged between 16 and 25 (M = 21, SD = 2.6) were analysed. It appears that an experience of spiritualism can be an active coping mechanism to compensate for both a need to understand and feel reassured in the face of fear of death, and a need for contact and interaction following, amongst other things, a death. However, most of these stories revealed episodes of anxiety linked as much to the experience itself as to the difficulty of managing the emotions arising from it. This anxiety calls into question the relevance of paranormal experiences as a possible coping device.